Long-term follow-up after surgical treatment of infective endocarditis in children with congenital heart diseases - L. Prokopovуch; O. Golovenko; M. Rudenko; S. Spysarenko; T. Malysheva; Y. Truba; V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2018)
The current work presents the experience of surgical treatment of infective endocarditis (IE) in children with congeni-tal heart diseases (CHD). During the period from Jan 2010 to Dec 2017 in Amosov National Institute of Cardiovascular Surgery, 32 children with IE and CHD were operated. The mean age of patients at operation was 11,6±5,7 years. Hospital mortality was 6,2% (2 patients). A total of 28 (93.3%) from 30 children who were discharged from the hospital were examined. The follow-up time was from five months to 10.1 years (5.9±2.5 years). The age of patients at the time of the examination varied from 2.1 to 24.3 years (17.1±7.8 years). There were two (7,1%) late deaths. The cumulative survival rate of patients at one year after the op-eration was 100%, 5 years – 96.2%, 10 years – 90.2%. In two (7.1%) patients, signs of IE were re-discovered. The proportion of patients without reoperations in the long-term follow-up at one year after surgery was 92.6%, 84.2% – at 5 years, 77.2% – at 10 years.